Androgen synthesis in menopause and diagnosis of causes of hyperandrogenism in menopause - О. А. Бурка; Т. М. Тутченко (Publishing House TRILIST, 2019)
Increasing life expectancy makes the issue of medical management of hormonal, cardiometabolic and cosmetic changes caused by menopause increasingly relevant. The manifestations and consequences of hyperandrogenism (HA) in women of perimenopausal and menopausal age, both in context of cardiometabolic disorders and dermatopathies, often cause difficulties in diagnosis and uncertainty in management among medical specialists. This literature review presents data from current studies on differences of synthesis, transport, and peripheral conversion of androgens in menopause in healthy women and in women with polycystic ovary syndrome, as well as on tumorous and non-tumorous causes of HA in menopause. Most menopausal women have a relative HA due to increased ovarian synthesis caused by high luteinizing hormone levels and progressive estrogen decline, as well as increase of bioavailable testosterone fraction caused by a decrease in sex hormone binding globulin. The causes of true (pathological) HA in menopause can be divided into non-neoplastic, represented by genetically determined syndromes (polycystic ovary syndrome, non-classical forms of congenital adrenal hyperplasia), ovarian hypertechosis, iatrogenic causes; and neoplastic causes - adrenal and ovarian tumors. Diagnosis of the causes of HA in menopause can be a difficult task, successfully solved by a comprehensive approach with the use of next steps: careful analysis of anamnestic data, the details of which may indicate the presence of pre-existing polycystic ovary syndrome or non-classical congenital adrenal hyperplasia; history of the disease (gradual or sudden development of HA as signs of tumorous or non-tumorous origin) examination and physical examination (objective assessment of the degree of HA, signs of insulin resistance or endocrinopathy), use of laboratory diagnostics (confirmation of biochemical hyperandrogenism and use of oncologic markers in case of suspicion of certain types of tumors); additional methods of examination (ultrasound, MRI) and in some cases functional tests.